Enhanced bioconversion of hemicellulosic biomass by microbial consortium for biobutanol production with bioaugmentation strategy. (May 2019) - Shanmugam, Sabarathinam; Sun, Chongran; Chen, Zichuang; Wu, Yi-Rui
Highlights: Consortium MC1 generate 6.51 g/L of butyrate and 0.11 g/L of butanol from xylan. Ruminococcus and Clostridium in MC1 were mainly involved in xylan transformation. Bioaugmentation strain WST with MC1 improved butanol yield to 98-fold. Established bioaugmentation system yield 1.09 g/L of butanol from untreated corncob. Abstract: As a renewable and sustainable source for next-generation biofuel production, lignocellulosic biomass can be effectively utilized in environmentally friendly manner. In this study, a stable, xylan-utilizing, anaerobic microbial consortium MC1 enriched from mangrove sediments was established, and it was taxonomically identified that the genera Ruminococcus and Clostridium from this community played a crucial role in the substrate utilization. In addition, a butanol-producing Clostridium sp. strain WST was introduced via the bioaugmentation process, which resulted in the conversion of xylan to biobutanol up to 10.8 g/L, significantly improving the butanol yield up to 0.54 g/g by 98-fold. When this system was further applied to other xylan-rich biomass, 1.09 g/L of butanol could be achieved from 20 g/L of corn cob. These results provide another new method to efficiently convert xylan, the main hemicellulose from lignocellulosic biomass into biofuels through a low-cost and eco-friendly manner.